2014
DOI: 10.1007/s00535-014-0995-2
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin suppresses LAMP-2 expression and induces lipophagy and lipoapoptosis in rat enterocytes via the ER stress pathway

Abstract: The findings of this study describe a novel mechanism of enterocyte damage by indomethacin mediated by endoplasmic reticulum stress, accumulation of LDs, and subsequent activation of the early phase of cytoprotective lipophagy. This is followed by a late phase characterized by reduced expression of lysosomal autophagic proteins, accumulation of ALPs, and enhanced lipoapoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 67 publications
(150 reference statements)
1
37
0
Order By: Relevance
“…This special type of selective autophagy is referred to as "lipophagy" [35] . Its major mechanism occurs after the fusion of autophagosomes and lysosomes when CEs in LDs are hydrolyzed by specific enzymes into free cholesterols, which can transfer through the cell membrane and then be carried by apoA-I or HDL in back to the liver [36,37] .…”
Section: Effects Of Macrophage Autophagy On Cholesterol Effluxmentioning
confidence: 99%
“…This special type of selective autophagy is referred to as "lipophagy" [35] . Its major mechanism occurs after the fusion of autophagosomes and lysosomes when CEs in LDs are hydrolyzed by specific enzymes into free cholesterols, which can transfer through the cell membrane and then be carried by apoA-I or HDL in back to the liver [36,37] .…”
Section: Effects Of Macrophage Autophagy On Cholesterol Effluxmentioning
confidence: 99%
“…In a previous study, Narabayashi et al (2015) reported that IM induced accumulation of cytoplasmic lipid droplets (LDs), and lipophagy (autophagic degradation of portions of LDs or whole LDs either alone or mixed with other cell contents) was promoted to remove the toxic LDs in IEC6 cells. To examine how autophagy (including lipophagy) is involved in IMinduced intestinal epithelial injury, we used Atg5-CKO mice in which autophagy did not occur only in intestinal epithelial cells.…”
Section: Evaluation Of Intestinal Epithelial Injury In Wt Andmentioning
confidence: 99%
“…Since autophagy is reported to take place after IM treatment as well as apoptosis in IEC6 cells (Narabayashi et al, 2015), we focused on autophagy and examined the role of autophagy in intestinal epithelial damage. Here, we showed that prevention of autophagy reduced apoptosis-mediated, IM-induced intestinal epithelial cell damage.…”
Section: Amelioration Of Indomethacin-induced Injury By Autophagy Defmentioning
confidence: 99%
“…ER stress was also observed in cultured rat enterocytes treated with indomethacin (Narabayashi et al. 2015). …”
Section: Introductionmentioning
confidence: 99%